Novel Poly(Benzonorbornadiene) Derivatives Prepared by a Three‐Dimensional Geometry Bimetallic Nickel Catalyst with Good Processability for Electrospinning. Issue 4 (19th July 2013) - Huo, Ping; Liu, Wanyun; He, Xiaohui; Chen, Yiwang
Abstract Two novel benzonorbornadiene derivatives (OAc)2BenzoNBD and (OCH2PhBr)2BenzoNBD monomers are synthesized and applied to copolymerize with 2‐butoxymethylene norbornene (BN) by the catalytic system of three‐dimensional geometry bimetallic nickel complex/B(C6F5)3. The (OCH2PhBr)2BenzoNBD or (OAc)2BenzoNBD content in the copolymers can be controlled 9.1–26.7% or 9.7–30.4% by varying the comonomer feed ratios (OCH2PhBr)2BenzoNBD or (OAc)2BenzoNBD from 10 to 50%, respectively. Both of the poly(BN‐co‐(OCH2PhBr)2BenzoNBD)s and poly(BN‐co‐(OAc)2BenzoNBD)s exhibit high thermal stability and high glass transition temperature, as well as excellent optical transparency. Copolymers are processed into films and fibers by solution casting method and electrospinning, respectively. The films show good transparency in the visible region while the fibers are uniform with smooth surface and diameters ranging from 700 to 1 200 nm.<inline-graphic xlink:href="ark:/27927/pgg55mvwsfw" content-type="mame201300193-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />